New Generation Solar PV Powered Sailing Boat using Boost Chopper - Soumya Das; Pradip Kumar Sadhu; Suprava Chakraborty; Nitai Pal; Gourav Majumdar (Institute of Advanced Engineering and Science, 2014)
The objective of this paper is to establish technical and economical aspects of the application of stand-alone photovoltaic (PV) system in sailing boat using boost chopper in order to simplify the power system and minimize the cost. Performance and control of dc-dc converter, suitable for photovoltaic (PV) applications, is presented here. This converter is mainly boost converter feeding a dc load. However, for integration purpose only one inductor is sufficient for power conversion in the converter. Here, the boost converter extracts complete power from the PV source and feeds into the load. Furthermore, the PV panel provides the essential protection to the passengers of boat from the straight sunshine and also from the rainwater.